Ultrafast photo-thermal switching of terahertz spin currents - Agarwal, Piyush (2022)
Dissipationless and scattering-free spin-based terahertz electronics is the futuristic technology for energy-efficient information processing. Femtosecond light pulse provides an ideal pathway for exciting the ferromagnet (FM) out-of-equilibrium, causing ultrafast demagnetization and superdiffusive spin transport at sub-picosecond timescale, giving rise to transient terahertz radiation. Concomitantly, light pulses also deposit thermal energy at short timescales, suggesting the possibility of abrupt change in magnetic anisotropy of the FM that could cause ultrafast photo-thermal switching (PTS) of terahertz spin currents. Here, a single light pulse induced PTS of the terahertz spin current manifested through the phase reversal of the emitted terahertz photons is demonstrated. The switching of transient spin current is due to the reversal of magnetization state across the energy barrier of the FM layer. This demonstration opens a new paradigm for on-chip spintronic devices enabling ultralow-power hybrid electronics and photonics fueled by the interplay of charge, spin, thermal, and optical signals.